Developmental pressure and nutrient concentrations of Sungai Petani catchment, Kedah - Ismail, Wan Ruslan; Ibrahim, Mohd Nazrul; Willy, Rozana (2015)

(untitled)
Developmental pressure is encroaching many small towns and cities in Malaysia. The wave of development has caused small towns like Sungai Petani Town and its surrounding catchment area to be affected by the changing land uses due to developmental pressure in the catchment area. This paper examined the temporal patterns of nutrient concentrations longitudinally along the Sungai Petani River from March 2012 to December 2013 due to the unequal distribution of ‘green’ areas with respect to the ‘grey’ areas. Four stations were chosen longitudinally from upper Sungai Petani River downstream towards Sungai Petani Town and were monitored from upstream part of Sungai Petani Town which is the least affected station, through Sungai Petani Town and towards the downstream station below the Sungai Petani Town. Water sampling at all stations were performed through grab sampling technique at depths of about 0.5 m. Water samples were analysed only for dissolved forms of nitrate (NO3), ammoniacal nitrogen (NH4), total nitrogen (TN), phosphate (P04) and total phosphorus (TP).The samples were analysed using standard procedure by Adams (1989) and APHA (1998). Most of the nutrient concentrations increased from upper station to the second station situated in the Sungai Petani Town. Nitrate increases by 6 per cent and 15 per cent in 2012 and 2013 respectively, ammonia increases by 11 per cent and 35 per cent respectively, TN by 16 per cent and 22 per cent respectively, TP by 45 per cent and 44 per cent respectively, and PO4 by 13 per cent and 90 per cent respectively. On the other hand, the concentration decreases from second to the last station at the outlet downstream of the town. Nitrate decreases by 16 per cent and 27 per cent in 2012 and 2013 respectively, ammonia increases by 28 per cent and 44 per cent respectively. TN by 34 per cent and 41 per cent respectively, TP 16 per cent and 28 per cent respectively, and PO4 increases another 2.4 per cent in 2012 but decline by 42 per cent in 2013. The effect of urbanisation and development is clearly the main cause of the deteriorating water environment as shown by the increasing nutrient concentration along the Sungai Petani River where most of the parameters are above the permissible threshold limit.